Chemical warfare agent NOVICHOK - mini-review of available data - Nepovimova, Eugenie; Kuca, Kamil (Food and chemical toxicology, 2018)
The Cold War period is characterized by the infighting between the Western countries and the USSR in diverse areas. One of such fields was development of the weapons of mass destruction. Within various programs on both sides, a wide scale of different agents have been developed. However, information about some of them are still protected under the designation "top secret". Notwithstanding, in history several cases are known when such information beheld the daylight. One of such cases was the program FOLIANT and NOVICHOK. Both programs were developed by the USSR as a reaction to English/American invention of VX agent. If at least a part of available information is truthful, we can allege that these compounds belong among the most toxic synthetic agents ever. Within this contribution, we have reviewed available Eastern and Western data about the A-agents and their precursors, so-called NOVICHOKs, including their history, synthesis, physical-chemical properties, pharmacological characteristics and clinical manifestation.
Keywords: FOLIANT; Nerve Agents; USSR; nervová bojová látka; dějiny 20. století; organofosfáty; Chemical Warfare Agents; Humans; SSSR; NOVICHOK; History, 20th Century; lidé; dějiny 21. století; Organophosphates; Nerve agent; Chemical warfare agent; History, 21st Century; chemické bojové látky